FADD, Caspase-3, and Caspase-8 and Incidence of Coronary Events - Xue, Ling; Borné, Yan; Mattisson, Ingrid Yao; Wigren, Maria; Melander, Olle; Ohro-Melander, Marju; Bengtsson, Eva; Fredrikson, Gunilla Nordin; Nilsson, Jan; Engström, Gunnar (Arteriosclerosis, thrombosis, and vascular biology, 2017)
OBJECTIVE—To investigate the relationship between 3 markers of apoptosis, that is, FADD (Fas-associated death domain–containing protein), caspase-3, and caspase-8, and incidence of coronary events (CEs) in a population-based cohort study. APPROACH AND RESULTS—In vitro experiments were performed to assess the response of the apoptotic biomarkers after Fas stimulation of peripheral blood mononuclear cells. The experiments showed significantly increased releases of FADD, caspase-3, and caspase-8 after Fas stimulation. The relationship between FADD, caspase-3, and caspase-8, respectively, and incidence of CEs was studied in 4284 subjects from the population-based Malmö Diet and Cancer Study. Cox’ proportional hazards regression was used to examine the association between the apoptotic biomarkers and incidence of CE over a mean follow-up of 19 years. A total of 381 individuals had CE during the follow-up. High FADD at baseline was significantly associated with incident CE. In the highest compared with the lowest quartile of FADD, the risk factor adjusted hazards ratio for CE was 1.82 (95% confidence interval, 1.35–2.46; P for trend =0.001). A significant association was also found between caspase-8 and CE; the hazards ratio (Q4 versus Q1) was 1.90 (95% confidence interval, 1.39–2.60; P for trend =0.001) after adjustment for risk factors. No association was found between caspase-3 and CEs. CONCLUSIONS—High levels of FADD and caspase-8, but not caspase-3, were associated with increased incidence of CE in subjects from the general population. The in vitro experiments support the view that these biomarkers could reflect activation of the extrinsic apoptotic pathway.